Ageism During the Covid-19 Pandemic: Discussion and Recommendations - Hanife Andaç Demirtaş Madran (Connectist Istanbul University Journal of Communication Sciences)
The spread of the coronavirus disease 2019 (Covid-19) was labeled a “pandemic” by the World Health Organization on March 11, 2020. It has caused not only health-related issues but also economic, educational, psychological, and social problems. Further, discrimination associated with the pandemic has been observed around the globe. Besides the obvious negative consequences faced by the individuals targeted, pandemic-related discrimination has affected the spread of the virus by influencing public attitudes toward disease prevention and the restrictions imposed by authorities. Discrimination toward foreigners, minorities, and certain religious groups (e.g., Muslims) increased during this period. Additionally, the pandemic saw ageism spread rapidly to become more visible than ever. Acknowledging that Covid-19 poses a higher risk for individuals over a certain age, several countries implemented restrictions specific to those age groups. However, this practice resulted in the emergence of problems that were not considered initially, especially the escalation of ageism. This study examines ageism during the Covid-19 pandemic based on major theories and current research. First, discrimination and ageism are defined in detail. Then, pandemicrelated ageism is discussed within the framework of basic theoretical approaches. Finally, recommendations for preventing ageism related to the pandemic and in general are presented.